Perpu ke Undang-undang: Meneliti Implikasinya dalam Pembentukan Regulasi Hukum - M. Fajrul Falah; Supriyadi Supriyadi; Susianto Susianto (The Indonesian Journal of Islamic Law and Civil Law, 2025)
One of the topics that legal scholars discuss most often is the discussion of Government Regulation in Lieu of Law (Perppu) using the language of compelling urgency. It is important to stress once more that we detect the absence of a clear and present element in the issue of a Perppu in more than one instance. This becomes problematic because our legislation does not provide a precise definition of compelling urgency, which leaves room for the President to interpret it in a variety of ways when issuing a Perppu. Using a statute method and a conceptual approach based on cases that have emerged throughout the establishment of Perppu, normative legal research will be used to evaluate this issue. With an emphasis on the requirements for compelling urgency as the ratio legis (legal rationale) underlying their formation, the study examines the paradigm behind the issue of numerous Perppu across various governmental periods. According to the study's findings, the President's power to issue a Perppu is based on the constitutional criterion of compelling urgency. There are two general requirements for compelling urgency: urgency and the existence of a catastrophe. A disruption that results in an abrupt and serious emergency is considered a crisis (a terrible and sudden disturbance). Additionally, it states that three material elements must be met in order to issue a Perppu: beyond a reasonable doubt, limited time, and reasonable necessity. A number of the President's Perppu show a propensity to read compelling urgency as a pressing matter requiring legislation-level regulation. But the President's subjective perception still plays a significant role in Perppu's creation, especially when it comes to identifying the element of compelling urgency.